2006
DOI: 10.1089/cmb.2006.13.1546
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis Generation in Signaling Networks

Abstract: Biological signaling networks comprise the chemical processes by which cells detect and respond to changes in their environment. Such networks have been implicated in the regulation of important cellular activities, including cellular reproduction, mobility, and death. Though technological and scientific advances have facilitated the rapid accumulation of information about signaling networks, utilizing these massive information resources has become infeasible except through computational methods and computer-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
(34 reference statements)
0
25
0
Order By: Relevance
“…Several studies have used PPI networks to find optimal sets of targets for affecting disease processes while minimizing side effects [19,55,68]. Ruths et al [55] identified minimum sets of nodes whose removal would block downstream communication from signalling nodes, and similarly, Dasika et al [19] identified sets of drug targets for blocking a specific cellular processes while minimizing effects on other processes.…”
Section: Identifying Target Setsmentioning
confidence: 99%
“…Several studies have used PPI networks to find optimal sets of targets for affecting disease processes while minimizing side effects [19,55,68]. Ruths et al [55] identified minimum sets of nodes whose removal would block downstream communication from signalling nodes, and similarly, Dasika et al [19] identified sets of drug targets for blocking a specific cellular processes while minimizing effects on other processes.…”
Section: Identifying Target Setsmentioning
confidence: 99%
“…For each of these results, we used the constrained downstream algorithm [14] to enumerate all paths between the two proteins in the model. This algorithm performs an exhaustive search of a pathway graph model for all paths connecting one set of proteins to another.…”
Section: Predicting Novel Pathways Based On Knockout Resultsmentioning
confidence: 99%
“…This approach is reasonable because a close relationship between integer programming and the set cover is known [12]. It should be noted that our approach is significantly different from that in [11]: (i) problems and network representations are different from each other, (ii) optimality of the solution is not guaranteed in [11], whereas optimality is guaranteed in our approach.…”
Section: Introductionmentioning
confidence: 95%
“…However, these techniques require statements about the property of individual reactions in networks, details of which are often unavailable. Ruths et al recently proposed a framework for computational hypothesis testing in which signaling networks are represented as bipartite directed graphs [11]. In their framework, each network contains two types of nodes: nodes corresponding to molecules and nodes corresponding to reactions.…”
Section: Introductionmentioning
confidence: 99%